2022
DOI: 10.1002/adfm.202203902
|View full text |Cite
|
Sign up to set email alerts
|

Altering Local Chemistry of Single‐Atom Coordination Boosts Bidirectional Polysulfide Conversion of Li–S Batteries

Abstract: Single-atom catalysts affording multifarious typed metal centers and varied coordination numbers are extensively employed in Li−S realm to promote redox kinetics. Nevertheless, the modulation of coordination environment pertaining to local atomic composition to dictate the catalytic efficiency toward sulfur electrochemistry, has remains meaningful yet unexplored thus far. In this contribution, a new type of single-atomic iron mediator with a designed FeN 3 P 1 coordination structure is reported to boost bidire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…The different electrodes were prepared and measured to explore the application potential for Li-S batteries. Figure 6 a shows the CV curves of three electrodes in a voltage range of 1.7 to 2.8 V at a scan rate of 0.1 mV s −1 [ 33 ]. It was found that the S/C@Bi 3 TaO 7−x cathode displays two typical cathodic peaks at 2.03 V (peak i) and 2.35 V (peak ii), which correspond to the reduction of sulfur into high-order soluble LiPSs and the subsequent conversion of the LiPSs to insoluble Li 2 S 2 /Li 2 S. The anodic peaks at 2.38 V (peak iii) are associated with reverse oxidation conversion from Li 2 S to LiPSs and finally to sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…The different electrodes were prepared and measured to explore the application potential for Li-S batteries. Figure 6 a shows the CV curves of three electrodes in a voltage range of 1.7 to 2.8 V at a scan rate of 0.1 mV s −1 [ 33 ]. It was found that the S/C@Bi 3 TaO 7−x cathode displays two typical cathodic peaks at 2.03 V (peak i) and 2.35 V (peak ii), which correspond to the reduction of sulfur into high-order soluble LiPSs and the subsequent conversion of the LiPSs to insoluble Li 2 S 2 /Li 2 S. The anodic peaks at 2.38 V (peak iii) are associated with reverse oxidation conversion from Li 2 S to LiPSs and finally to sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…P atoms are also employed to assist the realization of such dual coordination toward efficient electrochemical reaction. Huang et al [79] . devised an efficient polymerization‐carbonization strategy to fabricate N, P coordinated Fe single atoms for Li−S batteries.…”
Section: Coordination Modulation Strategiesmentioning
confidence: 99%
“…In another work, Wang et al [78] P atoms are also employed to assist the realization of such dual coordination toward efficient electrochemical reaction. Huang et al [79] devised an efficient polymerization-carboniza-tion strategy to fabricate N, P coordinated Fe single atoms for LiÀ S batteries. Figure 3a and b demonstrate that N and P atoms are successfully coordinated with single metal Fe moieties.…”
Section: Non-metallic Atom Typesmentioning
confidence: 99%
“…On the basis of this equation, we classified these materials into three types: strong adsorption ( E ad > 2.5 eV), moderate adsorption (1 eV < E ad < 2.5 eV), and weak adsorption ( E ad < 1 eV). To suppress the competitive interaction between long chain Li 2 S x ( x = 4, 6, or 8) and solvent molecules, , an efficient anchor material should bind long chain Li 2 S x more firmly than do solvent molecules DME and DOL to avoid degradation of cell performance. However, once the binding energy exceeds the cleavage energy of the Li–S bond, the LiPSs would decompose and hinder the effective utilization of S. , Therefore, a moderate binding strength for polysulfides is a prerequisite for designing ideal anchor materials.…”
mentioning
confidence: 99%